The Effects of Lead and Selenium on Melanoma Induction - Isabel Sá; Tânia Nogueira; Elisabete Cunha (University Library System, University of Pittsburgh, 2015)
Background: Melanoma is a malignant skin cancer and is one of the most aggressive malignancies in humans. Heavy metals, including lead, are known to cause cellular toxicity and have been studied for their potentials to induce apoptosis in tumor cells. Since selenium is considered to act protectively in cases of lead poisoning, this study focused on the effects of sodium selenite and lead chloride, both alone and combined, on melanoma cell apoptosis. Methods: This study was carried out by doing cell culture of melanoma cells (B16-F10 cell line) and using C57BL/6 mice. Melanoma cells suspended in lead (II) chloride, sodium selenite, or lead (II) chloride + sodium selenite solutions were injected subcutaneously to mice to induce tumor growth. After 12 days, tumors were excised and measured, followed by flow cytometry and a statistical analysis using a one-way ANOVA. Results: In the group of mice receiving a single injection of melanoma cells suspended in 10 μmol/l of lead (II) chloride, the growth of tumor was significantly slower than in the control group. In mice treated with lead (II) chloride 50 μmol/l and 100 μmol/l, no tumor was visible at the end of the experiment. With a single injection of lead (II) chloride and sodium selenite at concentrations ≥ 10 μmol/l, the weight and size of the tumor were substantially smaller than in the control group. Conclusion: The effect of lead (II) chloride on melanoma induction is dependent on the concentration of lead (II) chloride. Future applications may include the use of lead (II) chloride to increase apoptosis and necrosis in tumor cells and thus suppress tumor cells proliferation.